Improved electrical behavior of ZrO2-based MIM structures by optimizing the O3 oxidation pulse time. (January 2015) - Paskaleva, A.; Weinreich, W.; Bauer, A.J.; Lemberger, M.; Frey, L.
Abstract: The influence of oxidation pulse during atomic layer deposition (ALD) process on electrical and dielectric properties of metal–insulator–metal (MIM) structures with different ZrO2 -based (e.g. pure ZrO2, Al- and Si- doped ZrO2 ) high- k dielectrics and different thicknesses has been investigated. Strongly pulse-time dependent as well as independent phenomena are observed and their thorough analysis has given more insight on the processes taking place in these structures thus allowing further optimization of their electrical performance. Longer oxidation pulses produce films with larger thicknesses which may be related to the incorporation of excess oxygen in the layers and the formation of less dense films. Incorporation of Al and 10 s pulse time are the most beneficial and provide structures with the lowest leakage current. At high positive voltages a significant increase of current and a change of I – V curve shape with increasing pulse time have been observed. The possible processes which provoke this change have been discussed. The analysis of leakage current mechanisms reveals that neither incorporation of Al or Si in ZrO2 nor oxidation pulse time change the energy position of traps participating in the conduction process, hence the nature of these traps remains unaffected – it is a single positively charged oxygen vacancy in ZrO2 . The oxidation pulse time of 5–10 s is the optimal one which provides structures fulfilling the requirements for next generation MIM-based dynamic random access memories (DRAMs).